e-adaptation to climate change in Malawi - Mloza Banda, Catherine B. (Technical Centre for Agricultural and Rural Cooperation, 2014)
An ICT-enhanced participatory radio campaign in Malawi shows that ICTs can be easily integrated into the lives and work of smallholder family farmers